Study on the processing conditions, morphology and thermal properties of composites based on polyethylene and fly ash - Hoang, Thai nh; Giang, Nguyen Vu; Chinh, Nguyen Thuy (Vietnam Journal of Chemistry, 2012)
The composites based on high density polyethylene (HDPE) and linear low density polyethylene (LLDPE) 75/25 wt.% (abbreviated as PE) and fly ash (FA) were prepared by melt mixing at 85/15 wt.%. In order to improve the dispersion and adhesion of FA into PE matrix, FA was modified with vinyl trimetoxy silane (VTMS). The results showed the suitable conditions to prepare PE/FA composites are mixing temperature 180°C, mixing speed 50 rpm and mixing time 5 minutes. The study on morphology of PE/FA composites exhibited the dispersion, the adhesion and the interaction of modified FA (MFA) with PE matrix are better than those of original FA (OFA). The DTA, TGA curves showed the PE/MFA-OFA composite has low thermo-oxidation degradation rate and weight loss in comparison with those of PE and PE/OFA. That proved the role of MFA-OFA mixture in improving the thermal stability of PE.